(untitled) (International Journal of Studies in Nursing, 2018)
Following the Revolution of 1959, Fidel Castro declared healthcare a right for all Cuban citizens. In 1983 a pilot project was established which paired a family doctor and nurse to care for all persons within a neighborhood. The success of this project led to the establishment of the family doctor-nurse partnership to care for all Cuban citizens. Working together, the pair provided direct care, health assessment, risk management, and health promotion for a specified neighborhood. This novel way of providing primary care provides each Cuban with a family doctor and nurse. This arrangement has helped change the health of a nation.